2015
DOI: 10.1007/s10753-015-0239-5
|View full text |Cite
|
Sign up to set email alerts
|

Silencing Triggering Receptors Expressed on Myeloid Cells-1 Impaired the Inflammatory Response to Oxidized Low-Density Lipoprotein in Macrophages

Abstract: Atherosclerosis is a chronic progressive inflammatory disease characterized by the accumulation of lipid contents in arterial walls. Previous studies suggest participation of Toll-like receptors (TLRs) in lipid deposition and inflammatory response in vascular wall. The triggering receptor expressed on myeloid cells 1 (TREM-1) is a cell surface receptor of the immunoglobulin superfamily, which amplifies signal transduction of TLR pathway and enhances immune response to microbial infections. The aim of the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Mice treated by intrathecal administration of MIS416 (n = 17), at EAE onset, progressed less rapidly following 2 days than control animals(n = 12). c Cells isolated from brains of mice with EAE were analyzed by flow cytometry, at 24 h post intrathecal administration of MIS416 (n = [8][9][10][11][12][13][14][15][16][17][18][19]. Bar graph shows MIS416-induced recruitment of CD45 high cells in the CNS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice treated by intrathecal administration of MIS416 (n = 17), at EAE onset, progressed less rapidly following 2 days than control animals(n = 12). c Cells isolated from brains of mice with EAE were analyzed by flow cytometry, at 24 h post intrathecal administration of MIS416 (n = [8][9][10][11][12][13][14][15][16][17][18][19]. Bar graph shows MIS416-induced recruitment of CD45 high cells in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Increased phagocytic activity was supported by RNAseq data from MIS416-treated CNS, which showed upregulated levels of phagocytosis related genes, including MSR1 and TREM1. These are known to be expressed by monocytes and act as positive regulators of phagocytosis in these cells [8,15]. Extraparenchymal myeloid cells would be expected to take up MIS416 microparticles directly upon encounter in leptomeningeal space.…”
Section: Discussionmentioning
confidence: 99%
“…TREM‐1 connected and regulated complicated signals through several pattern recognition receptors induced by specific toll‐like receptor agonists in the inflammatory process 7, 8. Li et al27 identified that TREM‐1 was a certain epitope of oxidized low‐density lipoprotein in macrophages through the toll‐like receptor pathway, which facilitated foam cell formation and activated inflammatory response, suggesting a crucial role in further plaque progression and rupture. Silencing TREM‐1 by means of short hairpin RNA or linear plasmid 17 reduced lipid uptake and foam cell formation and impaired inflammatory response to oxidized low‐density lipoprotein 27.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al27 identified that TREM‐1 was a certain epitope of oxidized low‐density lipoprotein in macrophages through the toll‐like receptor pathway, which facilitated foam cell formation and activated inflammatory response, suggesting a crucial role in further plaque progression and rupture. Silencing TREM‐1 by means of short hairpin RNA or linear plasmid 17 reduced lipid uptake and foam cell formation and impaired inflammatory response to oxidized low‐density lipoprotein 27. The expression of TREM‐1 was also mostly found close to cholesterol‐ and necrotic‐rich areas.…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that the association between microbial infection and atherosclerosis involves common mechanisms of signaling via TLR2 and TLR4. Some investigators have proposed that TLR signaling induced by multiple pathogens and endogenous ligands may explain the link to atherosclerosis and that therapeutic TLR antagonism could prove beneficial in the treatment of chronic atherosclerosis (13, 14, 116118). However, our work revealed that P. gingivalis -mediated TLR4 signaling protects from atherosclerosis, suggesting that effects are pathogen specific.…”
Section: Innate Immune Mechanisms Linking Specific Microorganisms To mentioning
confidence: 99%